Stress with the Incidence of Hypertension in the Internal Care Room of the Jayapura Regional General Hospital - Tondok, Santalia Banne; Ruben, Sethiana Dewi; Hidayati, Laili Nur; Halitopo, Yoel; Swastika, I Ketut; Suabey, Suningsih (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Hypertension is a condition where a person experiences an increase in blood pressure above normal which results in morbidity (mordibility) and mortality/mortality. Blood pressure 140/90 mmHg is based on two phases in each heartbeat, namely the systolic phase of 140 mmHg indicating the phase of blood being pumped by the heart and the diastolic phase of 90 mmHg indicating the phase of blood returning to the heart. The purpose of this study was to determine the relationship between stress and the incidence of hypertension. The research method used in this study is a surveyanalytic study using a cross-sectional design, namely each respondent is only observed once and the measurement of the respondent's variables is carried out at the time of the examination. The population in this study were all patients with hypertension who were hospitalized in the Internal Medicine room, totaling 54 people. From the results of research on the relationship between stress and the incidence of hypertension in the Interna Treatment Room of Jayapura Regional General Hospital, it can be concluded that there is a relationship between stress and the incidence of hypertension in the Interna Treatment Room of Jayapura Regional General Hospital with a significant value obtained ρ < α (0.036 < 0.05).